Bridging together: teamwork in caring for the family touched by CHD. (29th December 2017) - Jonas, Richard A.
Abstract: In the opening plenary address of the 2017 7th World Congress of Pediatric Cardiology and Cardiac Surgery the author, who represented the World Society for Pediatric and Congenital Heart Surgery at the Congress and is currently the Society's president, described the history of the formation of the World Society. He listed accomplishments of the World Society including publication of the only journal devoted to congenital cardiac surgery, development of a global database, and convening several international conferences dating back to the inaugural conference in Washington, DC in 2007. The general theme of the presentation is the importance of teamwork in managing patients and families with CHD. Challenges facing congenital heart teams are discussed including the fragility of cardiac programmes, that can be heavily influenced by the administrative structure of a paediatric hospital; the difficulty of recruiting skilled surgeons into the field as training in general cardiothoracic surgery contracts and general surgery becomes predominantly laparoscopic with few open procedures; and increasing barriers to the international movement of surgeons including the opportunities for United States of America-based surgeons to acquire international experience at leading global centres. Finally, the author focusses on the danger that the team approach poses to maintaining empathy and emotional support for the family with CHD undergoing a stressful hospitalisation. He discusses strategies to optimise holistic support of the child and family.